Selection and identification of xylose-fermenting yeast strains for ethanol production from lignocellulosic biomass - Araújo, Juliana Alves; Abreu-Lima, Thiago Lucas de; Carreiro, Solange Cristina (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2019)
Ethanol production from lignocellulosic biomass is of economic interest due to the pressure to reduce fossil fuels consumption and land use for non-edible crops. Xylose is one of the main sugars obtained by hydrolysis of hemicellulose fraction of biomass, but industrial yeasts cannot ferment it. This work aimed to select, characterize and identify xylose-fermenting yeasts from Brazilian microorganisms collections with potential use in ethanol production. Xylose assimilation was tested by replica plating, and fermentation was tested with Durham tubes. Xylose-fermenting strains had their fermentative capacity quantified and compared to a reference strain (Scheffersomyces stipitis UFMG-IMH 43.2) and were identified by molecular techniques. Three strains isolated from plant exudates were able to ferment xylose and showed fermentative parameters similar to the reference strain. Two strains were identified as Candida parapsilosis and one was identified as Meyerozyma guilliermondii. The findings show the potential biotechnological use of these microorganisms.